Contextualizing some popular hockey analytics charts - Way, D. (2018)
Hockey analytics continue to be a polarizing topic among hockey fans and media. While there are a multitude of reasons as to why some fans aren't big proponents of the advanced statistical measures available today, one particular issue continues to rise to the top: hockey analytics can be very difficult to understand and contextualize. While I staunchly disagree with the notion that "we've had nothing but Corsi-based stats for almost a decade," he does bring up a very valid point at the end of the tweet regarding the lack of context that accompanies the various graphics and data visualizations that get bandied about social media and blogs. While it isn't feasible for fans or analysts to attempt to fully explain every graphic every time they tweet one out, particularly for more data-rich visualizations such as Bill Comeau's SKATR player comparison tool, there is absolutely a need for further context and explanation for many of the excellent player analysis visualization tools that are available to the public. Consider this article my attempt to try to bridge this gap a bit, and provide that additional context and explanation that individuals like Neil Greenberg are looking for. In this piece, I will provide explanations for how to access, use and interpret a variety of the more popular hockey data visualization tools that are publicly available. If you still have questions about any of the charts I highlight, or if I left one out that you were hoping to learn more about, please don't hesitate to reach out to me on Twitter, and I will do my best to answer any questions you have. If there is enough demand for it, perhaps I'll write a part-two that provides explanations of a handful of other great hockey charts and data visualization tools out there.